Answers

2014-04-06T15:24:07+05:30
Hey friend it is very easy 
for eg-if you are given an equation2x^2+5x+3=0
then firstly you should take a pair of numbers whose multiplication is equal to 6x^2 (that means the multiplication should be equal to multiplication of first and last term of the equation which are 2x^2 and 3)and the sum/subtraction should be equal to the middle term which is equal to 5x in this equation
the number will be 2x and 3x. it is not necessary that the two numbers are always the first and last terms of the equation. some times their multiplication is not equal to the middle term of the equation 
so the solution of the above equation will be
2x^2+5x+3=0
2x^2+2x+3x+3=0
2x(x+1)+3(x+1)=0
(2x+3)(x+1)=0
and  the roots will be x= -1 and x= -3/2
2 5 2
2014-04-07T11:48:49+05:30
Let a+b+c be the equation
then, in the equation
b = sum......(1)
and
 a*c = product..........(2)
now find two nos. which on adding results in (1)
and 
on multiplying results in (2)
0